Simple Yet Effective Learning Media: Flashcard for the Circulatory System - Ramadhani, Dea Putri; mellisa (Perspektif Pendidikan dan Keguruan, 2025)
The results of observations and interviews conducted with teachers and students that there are still some materials that are difficult to understand and memorize especially on the material of the circulatory system, in the learning process the lecture method still dominates, and still uses textbooks/printed books, LKS, sometimes learning videos as media in the science learning process, so that the science learning process is less active and enjoyable. This study aims to develop a valid and practical flashcard learning media on the sub-material of the circulatory system for class VIII students of SMPN 38 Pekanbaru. This study is a development research (R&D) using the Plomp development model. Data collection instruments used are student and teacher interview sheets, student needs questionnaires, self-evaluation sheets, validation sheets, one-to-one evaluation test questionnaires, small group tests, field tests and validated observers. The sampling technique used is Simple Random Sampling. The results of the validation of material experts get an average of 88% with a valid category. The results of the validation of media experts get an average of 96% with a very valid category. The results of the validation of learning experts get an average of 100% with a very valid category. The practicality results averaged 88%, categorized as very practical. The conclusion is that the flashcard learning media for the circulatory system is categorized as very valid and very practical.